Comparative transcriptomic analysis reveals the regulatory mechanisms of catechins synthesis in different cultivars of Camellia sinensis. (July 2022) - Zhao, Li-Qiang; Shan, Chun-Miao; Shan, Ting-Yu; Li, Qing-Lin; Ma, Ke-Long; Deng, Wei-Wei; Wu, Jia-Wen
Graphical abstract: Highlights: We evaluated the genes involved in catechins biosynthesis in C. sinensis . In total, 47, 717 unigenes were obtained from two cultivars of C. sinensis . KEGG database analysis identified 13 key enzymes involved in catechins biosynthesis. The structures of LAR and ANR were spatially modeled. Our findings established a basis for further studies of catechins biosynthesis. Abstract: Camellia sinensis (L.) O. Kuntze is used to produce tea, a beverage consumed worldwide. Catechins are major medically active components of C. sinensis and can be used clinically to treat hyperglycaemia, hypertension, and cancer. In this study, we aimed to identify the genes involved in catechins biosynthesis. To this end, we analysed transcriptome data from two different cultivars of C. sinensis using DNBSEQ technology. In total, 47, 717 unigenes were obtained from two cultivars of C. sinensis, of which 9429 were predicted as new unigenes. In our analyses of the Kyoto Encyclopedia of Genes and Genomes database, 212 unigenes encoding 13 key enzymes involved in catechins biosynthesis were identified; the structures of leucoanthocyanidin reductase and anthocyanidin reductase were spatially modelled. Some of these key enzymes were verified by real-time quantitative polymerase chain reaction, and multiple genes encoding plant resistance proteins or transcription factors were identified and analysed. Furthermore, two microRNAs involved in the regulation of catechins biosynthesis were explored. Differentially expressed genes involved in the flavonoid biosynthesis pathway were identified from pairwise comparisons of genes from different cultivars of tea plants. Overall, our findings expanded the number of publicly available transcript datasets for this valuable plant species and identified candidate genes related to the biosynthesis of C. sinensis catechins, thereby establishing a foundation for further in-depth studies of catechins biosynthesis in varieties or cultivars of C. sinensis .